Investigating Regional Variation and Digital Dialect in Online Game Identity - Miswaty, Titik Ceriyani; Widhi, Bidari Andaru; Alawiyah, Rosidah; Elhia, Memy Wardhani; Nuralfilail, Nuralfilail (Journal of Languages and Language Teaching, 2024)
Online gaming communities are crucial for social interaction and communication among diverse groups worldwide. Language variation plays a crucial role in shaping individuals’ identities and social relationships within these communities. Based on those initial thoughts, this research is conducted with aims at examining the involvement of regional variations and digital dialects in the formation of identity within PUBG player groups. The approach used in this research is a qualitative anthropological approach. This approach was chosen because it focuses on human behavior and cultural phenomena which needs in-depth explorationof reallanguage analysis used in everyday communication in communities. Data collection techniques include observation, in-depth interview, and field notes and data analysis conducted using theme development, pattern recognition, and theme naming aided by Nvivo software in the coding process analysis. The finding of this research identified the formulation of digital dialects, influenced by repeated linguistic habits such as found in the way they use  and form slang lnguage and the adaptation of newcomers to community-specific language norms. Moreover, the research highlighted the role of language variation in fostering community bonding, enhancing in-group communication, and reflecting shared experiences among players. Overall, this research offers valuable understanding of the complex interplay among language, identity and community dynamic within online gaming realms which have never been explored by previous related research.